Uma aritmética para ensinar em manuais de didática da matemática, publicados no Brasil (1930-1960) - Carneiro, Rogerio dos Santos (2021)
The research carried out for the construction of this thesis aimed to analyze elements of arithmetic for teaching, present in Didactics of Mathematics manuals published in Brazil, between 1930 and 1960. Its central question is “which elements of an arithmetic for teaching are present in manuals of mathematics Didactics of Mathematics, published in Brazil between 1930 and 1960, aimed at training teachers for the first school years?”. The time period chosen corresponds to the period of highlight of the New School Movement in Brazil, which had a great impact on changes in primary education, teacher training, the production of pedagogical manuals, among other actions related to education. This investigation sought theoretical and methodological contributions in research that have professional knowledge as a central theme, such as Hofstetter and Schneuwly (2017), Bertini, Morais and Valente (2017). Julia (2001), Chervel (1990), Burke (2016) contributed, respectively, with the concepts of school culture, history of school subjects, profession. Valente (2007, 2017, 2018, 2019), Pinto (2014, 2018, 2020), with contributions from the History of Mathematics Education. With this foundation, we analyze the pedagogical manuals, Arithmética na “Escola Nova” (1933), by Everardo Backheuser; The new methodology of arithmetic (1936), by Edward Lee Thorndike and Methodology of Mathematics (1951), by Irene de Albuquerque, works that were used in the training of primary teachers. The analysis of the sources indicates a strong presence of professional knowledge, arithmetic to teach in the first years of primary education, during the golden moment of the Escola Nova Movement in Brazil, from 1930 to 1960. In this sense, characteristic elements of an arithmetic to teach, such as the use of games and suitable manipulative materials for learning the contents, contextualization of teaching in everyday situations in the children's universe, mental calculation, problem solving and content graduation.